Individual and community-level factors of availability of observed water, soap, and other cleansing agents for hand washing practice in Ethiopia: a multilevel mixed-effects analysis of the 2021 performance monitoring for action Ethiopia - Kebede, Natnael; Delie, Amare Mebrat; Ketema Bogale, Eyob; Anagaw, Tadele Fentabel; Talie Fenta, Eneyew; Adal, Ousman (Frontiers in Public Health, 2024)
Introduction: This study delves into individual and community-level factors influencing the availability of water, soap, and cleansing agents for handwashing in Ethiopia. Its comprehensive exploration offers nuanced insights, informing targeted interventions and policies to enhance handwashing resources across Ethiopia effectively. Therefore, this study aimed to assess individual and community-level factors of availability of observed water, soap, and other cleansing agents for hand washing practices in Ethiopia.Methods: Data from the 2021 PMA-ET, encompassing 24,747 household participants, informed this study. Employing STATA version 17.0, a multi-level mixed-effect logistic regression analysis was performed to identify individual and community-level factors. Adjusted odds ratios with a 95% confidence interval conveyed the strength and direction of associations, with significance determined at P < 0.05.Results: Significant factors affecting handwashing resources availability: water, soap, and cleansing agents included education status such as Participants aged below 25 and between 25-64 (OR=1.38; 95% CI: 1.0891, 1.7631) and (OR=1.45; 95% CI: 1.1431, 1.8621) respectively, individuals with no formal education and those with only primary education were 40% and 39% less likely (OR=0.60; 95% CI: 0. 47191, 0. 77317) and (OR=0.61; 95% CI: 0. 46526, 0. 80124) respectively, those who had poor and had middle wealth status were (OR=0.30; 95% CI: 0. 24955, 0.37165) and (OR=0.37; 95% CI: 0.31465, 0. 44973) respectively, who had media exposure (OR=2.88; 95% CI: 2.5565, 3.2615), water sources, various sources like Piped Water, tube well, dug well, spring, rainwater, and surface water were less likely to provide access compared to bottled water. Furthermore, clusters with a lower proportion of primary education (AOR = 0.13, 95% CI :( 0.04303, 0.44515)), and those with a higher proportion of middle wealth status (AOR = 3.26, 95% CI :( 1.071, 9.9245)).The study uncovered individual and community-level factors impacting the availability of water, soap, and cleansing agents for handwashing in Ethiopia. Personal factors like age, education, wealth, water source, and media exposure, Community factors such as education levels and wealth status showed significant associations. Community initiatives should boost primary education and equitable wealth distribution to ensure widespread access to hand-washing resources, fostering improved hygiene practices.